Molekulare Medizin? Anmerkungen zur Ausweitung und Redefinition des Konzepts der genetischen Krankheit - Lemke, Thomas (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
Politicians and scientists claim that today we live in an era of molecnlar medicine in which genetic knowledge will become more and more relevant for diagnosis, prevention and treatment of many diseases. This contribution analyses one central element in this alleged paradigm shift: the concept "genetic disease". It points to some serious limitations and flaws of the current usage of the notion "genetic disease" and stresses the performative and strategic dimension of molecular medicine. The search for genetic causes for diseases aligns with the contemporary political context that increasingly shifts responsibility for human misfortune and misery from social conditions to the individual.